James J. Dinsmore letter to Thomas H. Kent regarding bird sightings, February 4, 1980 - Dinsmore, James J.et al (1980)
Field notes contributed by James J. Dinsmore in a letter to Thomas H. Kent, February 4, 1980. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1979-1980. Epson - sheet feed/flatbed